Jurnal Kata: a poet builds a nation: hafez as a catalys in emrsons process of developing american literature - Behnam Mirzababazadeh Fomeshi, Adineh Khojastehpour (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
numerous studies have tried to elucidate the relationship between emerson and hafez.